Continuity and change in the applied anthropology of risk, hazards, and disasters. Issue 1 (May 2016) - FAAS, A. J.
Abstract : This article introduces the special issue of The Annals of Anthropological Practice on "Continuity and Change in the Applied Anthropology of Risk, Hazards, and Disasters." After reviewing the factors that account for the heightened anthropological attention to disasters in the early 21st century, I review each of the contributions to the special issue. The topics included in the special issue represent some of the simultaneously perennial and currently pressing issues in the anthropology of risk, hazards, and disaster: vulnerability, resilience, culture change, culture in practice, risk reduction, disaster capitalism, and response and recovery. The objective of this special issue is to help provide an orientation to the theoretical and applied tools that will help anthropologists better prepare to assist in disaster contexts. It will assist those that may be encountering these issues for the first time, as well as those already working in disaster‐affected communities.